Functional Characterization of Odorant Binding Protein 27 (RproOBP27) From Rhodnius prolixus Antennae - Oliveira, Daniele S.; Brito, Nathália F.; Franco, Thiago A.; Moreira, Monica F.; Leal, Walter S.; Melo, Ana C. A. (Frontiers in Physiology, 2018)
Olfactory stimuli can trigger a wide range of essential behaviours for the survival of Rhodnius prolixus, one of the main vectors of Chagas disease. Thus, information about proteins involved in Rhodnius olfaction might be helpful for the development of new vector control strategies. Odorant-binding proteins (OBPs) are small soluble proteins involved in the transport of odour molecules through the sensillum lymph to odorant receptors (ORs), which are housed on the dendritic membrane of olfactory sensory neurons. Here, we aimed for identification and functional characterization of OBPs from Rhodnius prolixus. Genes of interest were selected using conventional bioinformatics approaches and then quantitative PCR. The first screening was used to estimate the expression of 17 OBPs in different tissues of adult insects and revealed that 11 OBPs were expressed in all tissues, whereas 6 OBP genes were specific to antennae. Quantification of transcripts showed that RproOBP6 and RproOBP13 were expressed in both male and female antennae thus suggesting that they may be related to the recognition of semiochemicals which evoke behaviours common to both sexes, such as finding a blood meal. RproOBP17 and RproOBP21 were more expressed in female antennae, indicating they might be involved in female specific response behaviours, such as detection of oviposition attractants. In contrast, RproOBP26 and RproOBP27 genes were significantly more expressed in male than in female antenna, indicating that these proteins could play a role in male specific behaviours, such as orientation modulated by sex pheromones emitted by females. Lastly, we silenced RproOBP27 using RNAi, and examined the phenotype through behavioural bioassays and quantitative PCR. Adult males injected with dsOBP27 spent significantly less time close to females when compared to controls. Docking analysis between RproOBP27 and the most abundant chemicals identified in female metasternal glands suggested a favourable binding according to low values calculated for Gibbs free energy. We have therefore concluded that RproOBP27 might be involved in the reception of semiochemicals involved in sexual behaviour.